Sensory mapping of pelvic dermatomes in women with interstitial cystitis/bladder pain syndrome. Issue 1 (19th June 2017) - Sanses, Tatiana; McCabe, Patrick; Zhong, Ling; Taylor, Aisha; Chelimsky, Gisela; Mahajan, Sangeeta; Buffington, Tony; Hijaz, Adonis; Ialacci, Sarah; Janata, Jeffrey; Chelimsky, Thomas
Abstract : Aim: To describe a sensory map of pelvic dermatomes in women with Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS). We hypothesized that if IC/BPS involves changes in central processing, then women with IC/BPS will exhibit sensory abnormalities in neurologic pelvic dermatomes. Methods: Women with IC/BPS and healthy controls underwent neurologic examination that included evaluation of sharp pain sensitivity and vibration in dermatomes T12, L1, L2, S1‐5. Peripheral nervous system sensitivity to pressure, vibration, and pinprick were scored using numeric rating scales (NRS). Bilateral comparisons were made with Wilcoxon signed‐rank test and comparisons between groups were made by the Mann‐Whitney U ‐test. Results: Total of 74 women with IC/BPS and 36 healthy counterparts were included. IC/BPS and control groups had similar age (43.0 ± 14.1 and 38.6 ± 15.3 years, P  = 0.14) and BMI (28.9 ± 8.0 kg/m 2 and 26.9 ± 8.4 kg/m 2, P  = 0.24), respectively. Women with IC/BPS reported hyperalgesia (elevated bilateral NRS pain intensity) in all pelvic dermatomes compared to healthy controls. S4‐S5 region had the highest pain intensity in all participants. All IC/BPS participants exhibited vibration sensation hypoesthesia, at least unilaterally, in all of the pelvic dermatomes except L1 compared to healthy controls. Conclusion: This detailed map of neurologic pelvic dermatomes in women with IC/BPS found hyperalgesia in all pelvic dermatomes, and some evidence of vibration sensation hypoesthesia, compared to healthy controls. These findings support the hypothesis that IC/BPS may involve changes in central signal processing biased towards nociception.